PENGARUH LOCUS OF CONTROL INTERNAL, MOTIVASI KERJA, GAYA KEPEMIMPINAN TRANSFORMASIONAL, KOMITMEN ORGANISASI PADA KINERJA AUDITOR - Sendhi Rahayu, Ni Made Mas; Badera, I Dewa Nyoman (E-Jurnal Akuntansi; Vol 19 No 3 (2017), 2017)
The performance auditors is an action or implementation of inspection tasks that have been completed by auditor within a certain time. This study aims to obtain empirical evidence about the influence internal locus of control, motivation, transformational leadership and organizational commitment on performance auditor. This research was conducted in the Bali provincial public accounting firm registered in the Directory of Certified in 2016. The population in this study is the auditor who worked on Public Accounting Firm (KAP) with the number of respondents was 40 auditors. The sampling method used is the techniques nonprobability saturated samples. Data analysis used is multiple linear regression analysis. The analysis showed that the variables of internal locus of control, motivation, transformational leadership and organizational commitment influence positively and statistically significant in auditor performance. This means that the higher the internal locus of control, motivation, transformational leadership and organizational commitment, the higher the performance auditor.
Keywords: Internal LOC, Motivation, Leadership Styles, Organizational Commitment, Performance Auditor